The Analysis of the Forest Flora of the Strzyżowskie Foothills from the Perspective of Presence of Anthropogenic Species - Towpasz, Krystyna; Stachurska-Swakoń, Alina (Acta Universitatis Lodziensis. Folia Biologica et Oecologica, 2011)
The anthropogenic pressure of the forest communities of the Strzyżowskie Foothills (the Western Carpathians) was estimated on the basis of phytosociological materials. Carr communities are among the most threatened by invasive and alien species of the forest flora. The phenomenon of invasiveness of native species such as Calamagrostis epigejos or Carex brizoides was described. The highest number of ancient woodland indicator species was noted in the beech forest.